How biophilic design of the school outdoor environments impacts adolescents’ behaviour and psychology: A post-occupancy evaluation based on SEM - Mengqi Li; Na Li; Jie Yin; Leiqing Xu (Nature-Based Solutions, 2025)
Studies showed biophilic design enhances the restorative qualities of learning environments, reducing students’ stress and anxiety and benefiting their mental health. This study, guided by Kellert's biophilic design principles, examined the impact of eight biophilic design indicators across three dimensions—naturalness, aesthetics, and activity—on middle school students' physical activity, social interactions, and anxiety. It investigated how these factors contribute to reducing anxiety. Using a structural equation model, post-occupancy evaluation data from 275 adolescents were analyzed. The results show that the activity dimension directly influenced physical activity, which in turn affected anxiety and social interactions. Naturalness impacted physical activity and social interactions, while aesthetics negatively affected physical activity. The study highlights physical health as a key mediator and underscores the positive influence of naturalness and activity on anxiety reduction, contrasting with the negative impact of aesthetics. The findings suggest that integrating natural elements and promoting physical activity in school design may reduce adolescents ' anxiety.